The Influence of the Numbered Head Together Learning Model and the Talking Stick Model on Social Science Learning Motivation and Outcomes - Nursalam Nursalam; Muhammad Nawir; Nur Syahru Ramadhan; Suardi Suardi (Universitas of Muhammadiyah Makassar, 2023)
The main problem in this study is the method of teaching which is still not optimal, the lack of student learning motivation and the low student learning outcomes. Purpose: The purpose of this study is to apply the Numbered Head Together model and the Talking Stick Model to increase social studies learning motivation and outcomes. The research design used in this experimental research is quasi-experimental, using the Pretest-Posttest, Nonequivalent Multiple Group Design. This research uses two experimental classes. The first experimental class (X1) was treated using the Numbered Head Together model and the second experimental class (X2) was treated using the Talking Stick model. The sampling technique in this study was to use Nonprobability Sampling with a saturated sample. Research data analysis using descriptive analysis and inferential analysis.The results of the research show that there is no significant influence between the simultaneous learning model on the motivation and learning outcomes of Social Sciences for class V students at Kaluku Bodoa State Primary School with a significant value of 0.822 0.05, which means that H1 is rejected. H0 is accepted.